Avaliação da interação mãe-criança em contexto com e sem violência física conjugal: um estudo comparativo - D’Affonseca, Sabrina Mazo (Universidade Federal de São Carlos, 2013)
This dissertation was written in the form of a compendium of six scientific texts, which are articulated in order to discuss the impacts of partner physical violence on mother-child relationship. The first two papers present literature reviews. The first one revieweb the impact of domestic violence on mothering skills. The second one, the association between intimate partner violence and child maltreatment, two phenomena commonly associated, but which are commonly analyzed separately. The third paper aimed at comparing the dimensions of discipline practices of mothers victims and not victims of physical partner violence. The fourth article sought to examine the motherchild relationship in a situation of controlled observation laboratory, to investigate the specific impact of partner violence on the mother-child interaction. The fifth paper presents a review of a new cognitive construct to analyze the mother-child relationship, metaparenting, and the state of art about such constructo. Finally, the sixth paper compares the behaviors of metaparenting of female victims and not victims of physical violence. Overall, the data indicated that, when compared in relation to dimensiono of discipline and metaparenting, mothers victims of domestic violence and mothers without such a history, did not show statistically significant differences. When analyzing the impact of different variables on the mother-child relationship (Article 4), it was noted that the historical mother of child maltreatment and family income appear to be important variables to consider when analyzing the mother-child relationship.
Keywords: Violência familiar - prevenção; Violência conjugal; Violência física; Exposição à violência; Disciplina; Mães e filhos - relação; Partner violence; Children exposed to domestic violence; Mother-child relationship; Discipline; Observation; CIENCIAS HUMANAS::PSICOLOGIA